Defining Access Management in Health Care Delivery Organizations. Issue 3 (July 2021) - Hempel, Susanne; Hilton, Lara G.; Stockdale, Susan; Kaboli, Peter; Miake-Lye, Isomi; Danz, Margie; Rose, Danielle; Kirsh, Susan; Curtis, Idamay; Rubenstein, Lisa V.
Abstract : Managing patient access to care in health care delivery organizations is instrumental in shaping patient experiences. We convened an inclusive stakeholder panel, informed by evidence, to understand the dimensions and establish definitions of access and access management. The literature varies in access definitions, but the temporal measure "time to third next available appointment" was consistently used as an indicator of access. Panel deliberations highlighted the importance of patient-centeredness and resulted in comprehensive definitions for access management, optimal access management, and optimal access. Health care organizations and researchers can use the developed definitions and concepts as starting points for initiatives to improve access management. Abstract : Supplemental Digital Content is Available in the Text.